2014
DOI: 10.1111/jphp.12349
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of mitochondria in respiratory epithelial cells infected with human respiratory syncytial virus and functional implications for virus and cell biology

Abstract: Objectives The aim of this study was to quantitatively characterise the mitochondrial proteome of airway epithelial cells infected with human respiratory syncytial virus (HRSV), a major cause of paediatric illness. Methods Quantitative proteomics, underpinned by stable isotope labelling with amino acids in cell culture, coupled to LC-MS/MS, was applied to mitochondrial fractions prepared from HRSV-infected and mock-infected cells 12 and 24 h postinfection. Datasets were analysed using ingenuity pathway analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 93 publications
3
24
0
Order By: Relevance
“…The chaperone dependence of numerous viral proteins from the Mononegavirales remains to be defined (e.g., SH, VP24, NS1, NS2, M2-1, M2-2, V, and C). Proteomics studies frequently identify chaperones as interacting partners [11,76,79,82,93,112,120], but many times they lack validation of the interaction and formal testing of the relevance of the identified chaperone in the context of infection. Even for well-studied interactions, such as that of the NC with Hsp70, or the L protein with Hsp90, the role of co-chaperones or upstream and downstream chaperone systems remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chaperone dependence of numerous viral proteins from the Mononegavirales remains to be defined (e.g., SH, VP24, NS1, NS2, M2-1, M2-2, V, and C). Proteomics studies frequently identify chaperones as interacting partners [11,76,79,82,93,112,120], but many times they lack validation of the interaction and formal testing of the relevance of the identified chaperone in the context of infection. Even for well-studied interactions, such as that of the NC with Hsp70, or the L protein with Hsp90, the role of co-chaperones or upstream and downstream chaperone systems remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most druggable chaperone has been Hsp90. Work using various Hsp90 inhibitors has shown that non-toxic concentrations display antiviral activity against numerous Mononegavirales , including: the filovirus EBOV [110]; the paramyxoviruses PIV2 [88], MeV [86,111], MuV [80], and SV5 [88]; the pneumovirus RSV [62,79,87,112]; and the rhabdoviruses RABV [89] and VSV [88]. The successful inhibition of Hsp90 in humans for cancer treatment [26,43] highlights the feasibility of antiviral approaches that target chaperones.…”
Section: Chaperone Inhibitors As Antiviralsmentioning
confidence: 99%
“…SH, VP24, NS1, NS2, M2-1, M2-2, V, C). Proteomics studies have described some interactions with chaperones for a subset of these [11,75,87], as well as for better studied viral proteins [67,70,112,119]. However, these lack both validation and formal testing of a role in the viral life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the most druggable chaperone has been Hsp90. Work using various Hsp90 inhibitors has shown that non-toxic concentrations display antiviral activity against numerous Mononegavirales, including the filovirus EBOV [105]; the paramyxoviruses PIV2 [82], MeV [79,111], MuV [72], and SV5 [82]; the pneumovirus RSV [52,70,81,112]; and the rhabdoviruses RABV [83] and VSV [82]. The successful inhibition of Hsp90 in humans for the treatment of cancer [26,43] highlights the feasibility of antiviral approaches targeting chaperones.…”
Section: Chaperone Inhibitors As Antiviralsmentioning
confidence: 99%
“…[2] In another powerful application of proteomics, the paper by Munday et al explores how the syncytial viral infection of epithelial cells alters expression of mitochondrial proteins in a temporal manner. [3] While Tom was found to be protective, hsp90 supported epithelial cell infection by virus. [3] Such knowledge offers novel targets to explore in the development of anti-infective strategies.…”
mentioning
confidence: 99%